2018
DOI: 10.1111/are.13916
|View full text |Cite
|
Sign up to set email alerts
|

Egg hatching rate and fatty acid composition of Acartia bilobata (Calanoida, Copepoda) across cold storage durations

Abstract: To investigate egg storage capacity of the copepod Acartia bilobata for aquaculture interest, we tested hatching success rate (HSR) of inclusive eggs (mixture of all egg types) after 4°C storage. The HSR peaked after 14 days storage when incubating at 28°C for 48 hr (85.8 ± 1.6%) and 72 hr (87.6 ± 0.9%), then gradually declined until 1 year (48 hr: 7 ± 0.6%; 72 hr: 19.4 ± 3.9%). Reallocation of fatty acid profile suggests that docosahexaenoic acid (DHA) is correlated with the HSR of A. bilobata eggs. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Even under the arrested development stage the embryo still keeps some metabolic activities in the eggs, resulting in the deterioration of energy reserves (Nielsen et al, 2006). Similarly, Pan et al (2019) reported about the utilization of fatty acid resources in dormant eggs, which was considered as an indicator of metabolic activities for embryonic maintenance or development in A. bilobata . Hence, the conditions examined in the present study may not be sufficient to induce strong quiescence in a tropical species like A. tropica eggs and deterioration of energy reserves due to metabolic activities of the embryo might have affected the viability of A. tropica eggs beyond 48, as well as 72 h of storage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even under the arrested development stage the embryo still keeps some metabolic activities in the eggs, resulting in the deterioration of energy reserves (Nielsen et al, 2006). Similarly, Pan et al (2019) reported about the utilization of fatty acid resources in dormant eggs, which was considered as an indicator of metabolic activities for embryonic maintenance or development in A. bilobata . Hence, the conditions examined in the present study may not be sufficient to induce strong quiescence in a tropical species like A. tropica eggs and deterioration of energy reserves due to metabolic activities of the embryo might have affected the viability of A. tropica eggs beyond 48, as well as 72 h of storage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, the egg storage potential has been documented for A. bifilosa (Katajisto, 2004) and A. grani (Hansen et al, 2016). However, the studies regarding quiescence induction and subsequent reactivation in the eggs of tropical copepod species are limited to only A. bilobata (Beyrend-Dur et al, 2014;Pan et al, 2017Pan et al, , 2019. Further investigations are needed for standardization of induction of quiescence and subsequent reactivation in the eggs of local or regional species or strains of Acartia (Hansen et al, 2016).…”
mentioning
confidence: 99%
“…On the other hand, copepod quiescent eggs could be artificially induced and accumulated at cold conditions. Consequently, they could be transported and incubated to obtain newly hatched nauplii for first feeding of marine fish larvae similar to the practices with Artemia cysts (Drillet et al., 2006; Pan, Souissi, Hwang, & Souissi, 2017; Pan, Souissi, Sadovskaya, Hwang, & Souissi, 2019). Several copepod species from the genus Acartia can produce quiescent eggs despite their diverse geographical origins (Hansen, Buttino, Cunha, & Drillet, 2016).…”
Section: Figurementioning
confidence: 99%
“…The distinctive identifying character of the species is the presence of two lobes (bilobed) in third segment of the female fifth leg, adult males can grow up to 0.90–0.95 mm, and females to 0.95–1.10 mm with lifespan of 18 days (Abraham, 1970; Pan et al, 2014). In A. bilobata , mated females can produce eggs daily, with promising reproductive potential (24 eggs female −1 day −1 ; Pan et al, 2017, 2019). Different algal diets were successful in maintaining stable cultures (Pan et al, 2014); however, enhanced productivity and mass scale production of nauplii for use in larval rearing remains challenging and unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…The distinctive identifying character of the species is the presence of two lobes (bilobed) in third segment of the female fifth leg, adult males can grow up to 0.90-0.95 mm, and females to 0.95-1.10 mm with lifespan of 18 days (Abraham, 1970;Pan et al, 2014). In A. bilobata, mated females can produce eggs daily, with promising reproductive potential (24 eggs female −1 day −1 ; Pan et al, 2017Pan et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%